Wits student perceptions and attitudes of the South African National Health Insurance (NHI) policy reform - Heggenstaller, Alessandra Kim (My University, 2023)
South African healthcare is practiced within a two-tier system. This sees the public sector as run by government and the private sector which is supported in relation to an individual’s ability to contribute to a medical scheme—which is the main form of health insurance. Due to the absence of adequate coverage for many people in the developing world the World Health Organisation (WHO) has advocated the elimination of these gaps with the ultimate objective being Universal Health Coverage (UHC). This global initiative has been used to frame the rationale for a reconsideration of the South African health system. Their proposed systemic overhaul is broadly referred to as an attempt to achieve a single-payer National Health Insurance (NHI) policy reform (the White Paper, 2017). The primary goal of this policy is to ensure healthcare equity within an ethos of equality is provided to all South Africans. Functioning dynamics associated current South African political structures and agendas have put into question the reasonableness and rationale of NHI. This is particularly the case when reviewing the successes and shortcomings associated the nationalisation of private entities. State-owned Enterprises (SoE) have brought to light numerous limitations in how government maintains national infrastructure and delivers public services. Highlighted features of concern are bureaucratic maladministration, fraudulent and corrupt practices. It is from this point of view that questions are raised regarding the viability of the proposals. The policy proposals involve what appear to be extraordinarily complex interventions which raise questions about their appropriateness in context. Policy deliberations and technical appraisals are largely absent with very few people understanding both the proposals and the policy alternatives. It is within this context that this research seeks to examine how well members of the public understand the proposals—focusing on a relatively well-informed sub-group of university students. The research, therefore, seeks to examine if a relationship exists between tertiary students’ perceptions and attitudes in relation to their sense of knowledgeability in supporting, or even dismissing, the proposed NHI policy reform. Focus is given to students enrolled for the 2021 academic year at the University of Witwatersrand (Wits), Johannesburg, South Africa. The project was ethically approved by the Wits Human Research Ethics Committee (Non-Medical). To establish if a correlation exists between the student’s subjective/intersubjective opinions and his/her/their knowledge base, a mixed methods research design was used. A total of 211 online research survey responses were recorded and a total of 4 semistructured face-to-face interviews were conducted. The results indicate that knowledge transfer influenced how the students perceived and accepted the NHI proposals as well as the healthcare policy reform. Moreover, the terminology used to describe the technical processes related to the NHI Bill impact on how openly the students embraced the health systems change. In broad summary, the students expressed a lack of confidence in governments’ ability to improve the current healthcare sector.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Governance Public and Development Sector Monitoring & Evaluation to the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2021
Keywords: National Health Insurance (NHI); Two-tier healthcare system; Universal Health Coverage (UHC); UCTD; SDG-3: Good health and well-being